The two approaches to money: Debt, central banks, and functional finance - Giuseppe Mastromatteo; Lorenzo Esposito (Levy Economics Institute of Bard College, 2015)
The scientific reassessment of the economic role of the state after the crisis has renewed interest in Abba Lerner's theory of functional finance (FF). A thorough discussion of this concept is helpful in reconsidering the debate on the nature of money and the origin of the business cycle and crises. It also allows a reevaluation of many policy issues, such as the Barro-Ricardo equivalence, the cause of inflation, and the role of monetary policy. FF, throwing a different light on these issues, can provide a sound foundation for discussing income, fiscal, and monetary policy rules in the right context of flexibility in the management of national budgets, assessing what kind of policies should be awarded priority, and the effectiveness of tackling the crisis with the different part of public budget. It also allows us to understand ways of increasing efficiency through public investment while reducing the total operational costs of firms. In the specific context of the eurozone, FF is useful for assessing the institutional framework of the euro and how to improve it in the face of protracted low growth, deflation, and weak public finances.
Keywords: B22; E62; E63; 330; Crisis; Functional Finance; Debt; Growth; Sustainability of Public Finance; Central Bank Independence